A Literate Civilization - Zaprulkhan Khan (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2019)
In the electronic age today, the internet continues to experience innovation and development. The internet is bringing people increasingly into a beautiful world without limits called the digital era. This is the special service that digital technology presents to humans in this era. The most popular icon of digital technology is social media. Social media rose to the top of the digital technology products that are the most popular among the world's people today. Popping up various kinds of social media: Facebook, Twitter, Google+, Instagram, Path, Pinterest, Tumblr, Flickr, WhatsApp and more. The number of social media users abounds. The graph rose sharply in a short time to reach billions. According to experts, the world of social media is like a double-edged knife. On the one hand, it can provide a huge benefit for people who can use it well. But on the other hand, it can also cause harm, a bad impact for people who are not able to use it properly, well, and appropriately. This paper will explore the benefits of literacy, which is actively writing through social media platforms in various forms.